Hubungan Komunikasi Pemasaran di Media Sosial dengan Minat Berkunjung ke The Park Jabar - Galih Nugraha; Mochammad Rochim (Bandung Conference Series: Communication Management, 2024)
Abstract. The impact of technological developments in the field of communication and information has formed a digital society. Thus, social media, which is one form of digital media, can be utilized by business managers in the tourism sector to launch their marketing strategies. The Park Jabar is no exception, as one of the tourist destinations in Bandung. The content entitled "Seratus Ribu Dapat Apa" on Instagram @theparkjabar is one form of social media marketing carried out. Thus, it is necessary to know the extent to which the elements of entertainment, interaction, customization, E-WOM, and trendiness relate to visiting interest among the audience. In this study, researchers used the positivism paradigm with quantitative methods. The research approach uses the Rank Spearman correlation data analysis technique to determine the existence and strength of the relationship between the independent variable (X) and the dependent variable (Y). Primary data in this study were obtained from questionnaires distributed to 67 respondents, while secondary data used literature studies sourced from books, research articles, and credible online media. The results of this study indicate that there is a significant relationship between marketing on social media and visiting interest. The strength of the relationship is 0.868, which means that the relationship is in a very strong category. This is in line with the test results on sub-variable X, namely the relationship between entertainment, interaction, customization, E-WOM, and trendiness elements with visiting interest, which shows that there is a significant relationship between these elements and visiting interest with a strong relationship strength. Abstrak. Dampak perkembangan teknologi pada bidang komunikasi dan informasi telah membentuk masyarakat digital. Dengan begitu, media sosial yang merupakan salah satu bentuk media digital dapat dimanfaatkan oleh pengelola usaha di bidang pariwisata untuk melancarkan strategi pemasarannya. Tak terkecuali The Park Jabar, sebagai salah satu destinasi wisata di Kota Bandung. Konten berjudul “Seratus Ribu Dapat Apa” di instagram @theparkjabar menjadi salah satu bentuk pemasaran di media sosial yang dilakukan. Dengan demikian, perlu diketahui sejauh mana elemen entertainment, interaction, customization, E-WOM, dan trendiness berhubungan dengan minat berkunjung di kalangan penonton. Pada penelitian ini peneliti menggunakan paradigma positivisme dengan metode kuantitatif. Pendekatan penelitian menggunakan teknik analisis data korelasi Rank Spearman untuk mengetahui keberadaan dan kekuatan hubungan antara variabel bebas (X) dengan variabel terikat (Y). Data primer pada penelitian ini diperoleh dari angket yang disebarkan kepada 67 responden, sedangkan data sekunder menggunakan studi pustaka yang bersumber dari buku, artikel penelitian, serta media online yang kredibel. Hasil penelitian ini menunjukan terdapat hubungan signifikan antara pemasaran di media sosial dengan minat berkunjung. Kekuatan hubungan sebesar 0,868 yang berarti hubungan yang terjalin dalam kategori sangat kuat. Hal tersebut sejalan dengan hasil pengujian pada sub variabel X yakni hubungan elemen entertainment, interaction, customization, E-WOM, dan trendiness dengan minat berkunjung yang menunjukan bahwa terdapat hubungan yang signifikan antara elemen-elemen tersebut dengan minat berkunjung dengan kekuatan hubungan yang kuat.